Analisis Penghematan Bahan Bakar dengan Memanfaatkan Gas HHO - Abdu Idham; Mulianti Mulianti; Yolli Fernanda; Dori Yuvenda (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The scarcity of fuel that has an impact on the high selling price of fuel, then there needs to be an effort to save fuel in motor vehicles. The solution to this problem is to use renewable fuel, one of the renewable fuels is hydrogen gas. With the addition of renewable energy in the form of HHO gas (Hydrogen Hydrogen Oxygen) from water electrolysis. The purpose of this study was to determine the effect of the application of an electrolyzer on saving fuel consumption in motor vehicles. By using a quantitative method with an experimental research design to test the effect of two variables whether there is a change in the form of fuel savings before and after the installation of the electrolyzer tube. Based on the trials that the researcher has conducted, the results of the study were obtained, namely that the addition of an electrolyzer has an effect on the fuel consumption of 4-stroke motorcycles, both in static and dynamic tests. So with the addition of an electrolyzer, it will be able to save fuel consumption in motorcycles when compared to without using an electrolyzer